1999
DOI: 10.1088/0022-3727/32/21/309
|View full text |Cite
|
Sign up to set email alerts
|

Water-vortex stabilized electric arc: I. Numerical model

Abstract: A numerical model for an electric arc stabilized by a water vortex has been proposed. The two-dimensional axisymmetric model includes the discharge area between the cathode and the orifice of the arc chamber. The production of water plasma, i.e. the rate of evaporation of a water wall, is taken either from experiments or is determined numerically by fitting of the outlet plasma parameters to the experimental ones. The computer results concern thermal, fluid dynamic and electrical characteristics of such arcs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 15 publications
1
42
0
Order By: Relevance
“…In experiment, velocity at the nozzle exit is being determined from the measured temperature profile and power balance assuming local thermodynamic euilibrium . First, the Mach number M is obtained from the simplified energy equation integrated through the discharge volume (Jeništa, 1999b); second, the velocity profile is derived from the measured temperature profile using the definition of the Mach number regime (i.e., the mean value of the Mach number over the nozzle exit higher than 1) using this method was proved for 500 A and 40 slm of argon, as well as for 600 A for argon mass flow rates higher than 27.5 slm. Similar results have been also reported in our previous work (Jeništa et al, 2008).…”
Section: Comparison Of Radial Temperature and Velocity Profiles With mentioning
confidence: 99%
“…In experiment, velocity at the nozzle exit is being determined from the measured temperature profile and power balance assuming local thermodynamic euilibrium . First, the Mach number M is obtained from the simplified energy equation integrated through the discharge volume (Jeništa, 1999b); second, the velocity profile is derived from the measured temperature profile using the definition of the Mach number regime (i.e., the mean value of the Mach number over the nozzle exit higher than 1) using this method was proved for 500 A and 40 slm of argon, as well as for 600 A for argon mass flow rates higher than 27.5 slm. Similar results have been also reported in our previous work (Jeništa et al, 2008).…”
Section: Comparison Of Radial Temperature and Velocity Profiles With mentioning
confidence: 99%
“…( [23][24] These were solved by the SIMPLER iteration procedure (25) which enables calculation of w for the axisymmetric case, i.e., w is a function of r and z coordinates. The w velocity acts here only through the centrifugal force 2 w r ρ in the radial momentum equation.…”
Section: Boundary Conditions and The Numerical Methodsmentioning
confidence: 99%
“…The w velocity acts here only through the centrifugal force 2 w r ρ in the radial momentum equation. The influence of the tangential velocity component w on the overall arc performance was studied in greater detail in our previous papers (23)(24) but it was found that its effect on the arc performance is small. In fact, the maximum difference in the outlet parameters was less than 2% regarding the case which excludes the tangential velocity component.…”
Section: Boundary Conditions and The Numerical Methodsmentioning
confidence: 99%
“…Complex experimental data about properties of the arc and parameters of generated plasma were presented in [8][9][10][11], two-dimensional numerical model of Gerdien arc was formulated in [12,13].…”
Section: Introductionmentioning
confidence: 99%